Density functional theory calculations for estimation of gettering sites of C, H, intrinsic point defects and related complexes in Si wafers. (15th March 2016) - Shirasawa, Sho; Sueoka, Koji; Yamaguchi, Tadashi; Maekawa, Kazuyoshi
Abstract: Very recently, a C3 H5 cluster ion implantation technique for proximity gettering has been reported with the low energy of around 10 15 /cm 2 dose without recovery heat treatments. The main feature of this technique is that the gettering efficiency is higher than that by C monomer implantation, even though irradiation defects are too small to clarify by TEM observation. In the present work, we evaluate the binding energies of metal atoms with candidate gettering sites of C, H, intrinsic point defects and related complexes in Si wafers induced by C3 H5 cluster ion implantation or different methods, for example, H implantation etc. by using density functional theory calculations. In addition to C and H atoms, we consider donor P and O atoms contained in an n- CZ-Si wafer for use in a CMOS image sensor. The simplest complexes of substitutional/interstitial C (Cs /Ci ), Hi, Ps, Oi, and incorporated intrinsic point defects (vacancy ( V ) and self-interstitial Si ( I )) by C3 H5 implantation were also considered. We found that Cs – I (= Ci ), Ci –Ci, Hi – I, V Hn ( n =1–3), and V O complexes are the best candidates for gettering sites. Gettering by C3 H5 cluster ion implantation is more effective than that by C monomer implantation due to the formation of V Hn ( n =1–3) and Hi – I complexes, which provides more effective gettering sites.